Adequacy of energy and protein intake among hospitalized patients on therapeutic diet in government hospitals: A preliminary study. Issue 5 (2nd December 2019) - Kong, Jian Pei; Baharom, Basmawati; Jamhuri, Norshariza; Jamli, Khalizah; Mohd Yazid, Siti Farah Zaidah; Ashiquin, Norafidza; Isnin, Lina; Leow, Chooi Wah; Lim, Siew Mee
Abstract : Purpose: The provision of meals has long been regarded as an essential part of treatment of hospitalized patients complementing medical procedures and nursing management. Today, despite changes in the health-care landscape, which focused on improving the quality and efficiency of hospital care, malnutrition among inpatient was still a common worldwide concern. Design/methodology/approach: This was a multi-centre, randomized study conducted in 21 study sites comprising 21 state and specialist government hospitals under the Ministry of Health, Malaysia. The sample size for this study was calculated with purposive sampling method, followed by proportionate sampling to determine the random sample size of each of the study sites. The total sample size required for this study was 2, 759 subjects. A validated data collection form was used in the study. Findings: Only 32.2 % and 37.6 % of subjects achieved adequate energy and protein intake, respectively, during their admission to medical ward. The study result showed that the overall mean energy and protein intake was 794.6 ± 487.8 kcal and 35.2 ± 24.3 g, respectively. The estimated energy ( p = 0.001) and protein ( p = 0.001) intake of all study sites was significantly lower compared to the adequacy value. Research limitations/implications: The adequacy intake in this study was only carried out in medical wards, thus reproducible result among other wards in different study sites could not be confirmed. Besides, this study assumed that the portion eaten by subjects during lunch and dinner was the same, and therefore, either one was recorded together with breakfast and either lunch or dinner to represent a subject's daily intake. Originality/value: This was the first nationwide study to report the adequacy of energy and protein intake of patients receiving therapeutic diets in the government hospital setting in Malaysia.